Y Chromosome Microdeletions in Idiopathic Infertile Men from West Azarbaijan - Omrani, Mir Davood; Samadzadae, Saied; Bagheri, Mortaza; Attar, Kiarash (Urology Journal, 2009)
Introduction: Although assisted reproduction techniques are used extensively in Iran, screening for Y chromosome microdeletions before intracytoplasmic sperm injection is often undervalued. Our aim was to investigate Y chromosome microdeletions in men with idiopathic azoospermia or severe oligospermia. Materials and Methods: In 99 selected patients with azoospermia or severe oligospermia and elevated levels of follicle-stimulating hormone and luteinizing hormone in combination with low serum testosterone levels, 20 pairs of sequence-tagged site-based primer sets specific for the Y microdeletion loci were analyzed. Primers were chosen to cover azoospermia factor (AZF) regions as well as deleted in azoospermia (DAZ) and the sex-determining region on Y chromosome (SRY) genes. Also, 100 healthy men served as a control group. Results: Twenty-four patients (24.2%) had microdeletions in AZF genes, but no microdeletions were found in men in the control group. In 15 patients (62.5%), 1 deletion was found. Six patients (25%) had 2, and 3 (12.5%) had 3 deletions. The deletions mainly comprised the AZFc region (in 21 of 24 patients; 87.5%), which corresponds to the DAZ gene. Deletions in AZFb were found in 7 patients (29.2%), and 4 (16.7%) had deletions in the proximal part of AZF regions near SRY gene. No microdeletions were seen in the AZFa or SRY gene. Conclusion: Our results emphasize that Y chromosome microdeletion analysis should be carried out in all patients with idiopathic azoospermia or severe oligospermia who are candidates for intracytoplasmic sperm injection.